Internal and external barriers influencing LMS implementation in Iraqi higher education - Radif, Mustafa; Fan, Ip-Shing; McLaughlin, Patrick (Valencia IATED Academy, 2015)
Successful implementation of Learning Management System (LMS) can significantly improve the quality and quantity of education. Both the technological and people infrastructure need to be in place to achieve LMS success. Iraq is recovering from the recent wars and still faces serious security challenges. LMS could remove the time and geographic constraints of attending universities and bring education to more students, accelerating the re-skilling of the country. However, the Iraqi situation imposes specific context factors that are different from LMS implementation in developed countries. The aim of this paper is to identify the most important internal and external barriers in adopting LMS as a higher education initiative in Iraq, using the University of Al-Qadisiyah as the case organisation. The primary data collection targets are the IT staff, faculty and academic department heads because they are the key stakeholders to deliver the pedagogical and technological collaboration needed in successful LMS. There are 90 participants in the survey. The significant barriers to LMS implementation identified are: Lack of or limited teachers’ training; lack of commitment to constructivist pedagogy; lack of experience to use the technology; lack of technical support; lack of pedagogical training for teachers; and lack of appropriate educational software. Most important at this time is ICT skills development and ICT training provision for teachers. The correlation of these factors to the Iraqi context is discussed in the paper. The result is used to develop a framework on the internal and external barriers. This helps academic staff and IT staff to develop the teaching-learning style and achieve an effective adoption of LMS in all higher learning institutions in Iraq.
Keywords: Learning Management system; LMS